THE MEANING OF MANDAU IN DAYAK TUNJUNG-BENUAQ TRIBE IN EAST KALIMANTAN - Michael Makianggung (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2020)
The writer is interested to explore Mandau as the traditional weapon in East Kalimantan, especially in Tunjung-Benuaq. Mandau is the identity of Dayak tribes who inhabit in Kalimantan Island. In this article, the writer would like to describe about components and the process of making Mandau and the meaning of the symbols in Mandau in Dayak Tunjung-Benuaq tribes. The writer finds at least five kinds of accessories in a Mandau, they are a small knife, a woven rattan, a belt rope, hair and beads. Actually, not all the accessories in Mandau have a meaning or a symbol, but only a woven rattan and hairs on the sheath of a Mandau has symbol and a meaning according to local beliefs in a Dayak Tunjung-Benuaq tribe. Accessories like a small knife, a woven rattan, a rope belt and beaded are only added to the beauty purpose or for aesthetic. A small knife has a function as a carving tool and as back up weapon. That knife is put at the inside of the sheath. The woven rattan has a function as a belt to drape Mandau on waist. The woven rattan motif has a shape like circle. This circle means a balance of nature (based on the interview with Simon Malat). The last accessory is hairs on the hilt of a Mandau. According to local beliefs, the accessories mean bravery. The hair on the hilt of a Mandau symbolizes the bravery level of the owner. The people with a lot of hair in his Mandau will be more respected in society because the hair, a long time ago, was used on the hilt of a Mandau that came from mengayau ceremony.